Genetic Alteration in Phosphofructokinase Family Promotes Growth of Muscle-Invasive Bladder Cancer. Issue 3 (July 2016) - Sun, Chen-min; Xiong, Da-bo; Yan, Yang; Geng, Jiang; Liu, Min; Yao, Xu-dong
Aims: Metabolic alterations in cancer, including bladder cancer, have been addressed in recent years. We aimed to study the role of phosphofructokinase (PFK) in muscle-invasive bladder cancer (MIBC). Method: By in silico analysis of the bladder cancer data from the Cancer Genome Atlas (TCGA) database using the cBioPortal platform, we studied genetic alteration of genes within the PFK family (PFKL, PFKM, PFKP, PFKFB1, PFKFB2, PFKFB3, and PFKFB4). In vitro studies were carried out using the PFK inhibitor 2, 5-anhydro-D-glucitol-6-phosphate. Results: Genetic alterations of PFK family genes were observed in 44% of MIBC cases in TCGA. The main alterations were amplification and upregulation. Patients with altered PFK gene status were more likely to have a history of noninvasive bladder cancer. Altered PFK status was not associated with survival or disease relapse. Use of the PFK inhibitor significantly decreased the level of glycolysis and inhibited the growth and invasion of bladder cancer cells. Conclusions: PFKs were critical genes in charge of glycolysis and were upregulated in bladder cancer. Targeting this pathway could inhibit cell growth in bladder cancer.